2014
DOI: 10.1016/j.matbio.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The multiple, complex roles of versican and its proteolytic turnover by ADAMTS proteases during embryogenesis

Abstract: Embryonic development is an exceptionally dynamic process, requiring a provisional extracellular matrix that is amenable to rapid remodeling, and proteolytic or non-proteolytic mechanisms that can remodel the major components of this matrix. Versican is a chondroitin-sulfate proteoglycan that forms highly hydrated complexes with hyaluronan and is widely distributed in the provisional matrix of mammalian embryos. It has been extensively studied in the context of cardiovascular morphogenesis, neural crest cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 80 publications
2
138
0
1
Order By: Relevance
“…Colocalization of ADAMTS5 and versican immunoreactivity during embryonic development in the mouse lung at later stages of embryonic development (E16.5) has also been previously reported (McCullough et al 2009). With quantitative immunohistochemistry at E13.5, there was little DPEAAE accumulation in the lungs, suggesting antagonistic roles of versican deposition and versican proteolysis in promoting and inhibiting cellular growth and migration through a provisional extracellular matrix during development, as has been previously proposed in lung, cardiac and musculoskeletal system development and in lung inflammation (Kern et al 2006;Capehart 2010;Nandadasa et al 2014).…”
Section: Discussionmentioning
confidence: 54%
“…Colocalization of ADAMTS5 and versican immunoreactivity during embryonic development in the mouse lung at later stages of embryonic development (E16.5) has also been previously reported (McCullough et al 2009). With quantitative immunohistochemistry at E13.5, there was little DPEAAE accumulation in the lungs, suggesting antagonistic roles of versican deposition and versican proteolysis in promoting and inhibiting cellular growth and migration through a provisional extracellular matrix during development, as has been previously proposed in lung, cardiac and musculoskeletal system development and in lung inflammation (Kern et al 2006;Capehart 2010;Nandadasa et al 2014).…”
Section: Discussionmentioning
confidence: 54%
“…Whereas the proinflammatory cytokine TNF-α decreased rapidly, ADAMTS-1, an enzyme known to be associated with inflammation and versican processing, 82 changed minimally. To study versican turnover during the gradual decrease in hepatic inflammation and reversal of fibrosis, we assessed the appearance of versican cleavage products, G1-DPEAAE 441 (recently dubbed versikine 71 ) and G1-DPEAAE 1401 , which are generated by the ADAMTS proteoglycanases. We found that the versican V0 fragment was differentially produced during injury and recovery, but the more commonly described V1 fragment (versikine), changed little, with a significant decrease seen only at the 28 days of recovery time point.…”
Section: Versican In Liver Fibrosismentioning
confidence: 99%
“…70 Recently, the G1-DPEAAE 441 neo-epitope cleavage product of versican V1 has been dubbed 'versikine' to underscore the importance of versican cleavage in general and this versican cleavage product, in particular, in regulating tissue remodeling. 71 Given the known roles of versican in other tissues and the increases in CSPGs in liver remodeling, we hypothesized that versican expression would also play a role in the pathogenesis of hepatic fibrosis.…”
mentioning
confidence: 99%
“…2 We and others have previously demonstrated that versican (VCAN), a large, chondroitin-sulfate matrix proteoglycan, accumulates in myeloma lesions and have hypothesized that VCAN may contribute to myeloma niche immunoregulation. 3,4 VCAN has crucial, nonredundant significance in embryonic development 5 and emerging roles in cancer inflammation and metastasis. [6][7][8][9] VCAN promotes tolerogenic polarization of antigen-presenting cells through Toll-like receptor 2 (TLR2).…”
Section: Introductionmentioning
confidence: 99%